Investment efficiency, state-owned enterprises and privatisation: Evidence from Viet Nam in Transition - O'Toole, Conor M.; Morgenroth, Edgar L.W.; Ha, Thuy T. (Journal of Corporate Finance, 2016)
Our research firstly tests the difference in investment efficiency between state-owned enterprises (SOEs) and private firms and secondly evaluates the effect of privatisation and equitisation policies on the investment efficiency of former state owned enterprises (SOEs). We use a novel dataset from Viet Nam which covers large and non-listed SMEs across construction, manufacturing, and service sectors. Our methodology uses a structural model to test the relationship between Tobin's Q and capital spending. While evident differences in investment efficiency are found across heterogeneous groups of private firms (size, industry, financially constrained and location), we find no evidence of investment spending being linked to marginal returns by SOEs across all sectors and size classes. However, former SOEs that have been privatised and equitized with a minority state shareholding display positive links between Q and investment. In fact, the link is stronger for these firms than for private firms. Differences are also evident across size and sector highlighting that the method of divestment chosen by government shareholders has a differential impact on efficiency across groups of firms and industries.